The Oxford handbook of skills and training - Buchanan, John, 1959-; Finegold, David; Mayhew, Ken; Warhurst, Christopher (Oxford : Oxford University Press, 2017)
Skills and workforce development are at the heart of much research on work, employment and management. Policy makers and managers often consider the better development of skills to be the answer to a range of practical and policy challenges. This handbook sheds new light on all the major issues concerning skills and training today.
Disciplinary Perspectives on Skill / Jane Bryson -- What is Expected of Higher Education Graduates in the 21st Century? / Martin Humburg, Rolf Van der Velden -- Employer-led In-Work Training and Skill Formation: the Challenges of Multi-Varied and Contingent Phenomena / Lorna Unwin -- Unions, the Skills Agenda and Workforce Development / Mark Stuart, Tony Huzzard -- A Working Lifetime of Skill and Training Needs / Günther Schmid -- Skill Under-utilization / D. W. Livingston -- Business Strategies and Skills / David Ashton, Caroline Lloyd, Chris Warhurst -- Measuring Skills Stock, Job Skills and Skills Mismatch / Alan Felstead, Duncan Gallie, Francis Green -- The individual benefits of investing in skill / Craig Holmes -- The economic and social benefits of skills / Irena Grugulis, Craig Holmes, Ken Mayhew -- Theorising Skill Formation in the Global Economy / Hugh Lauder, Phillip Brown, David Ashton -- Skill Builders: The Evolution of National Vocational Training Systems / Cathie Jo Martin -- Different National Skill Systems / Gerhard Bosch -- Skill Ecosystems / John Buchanan, Pauline Anderson, Gail Power -- Employment Systems, Skills and Knowledge / Alice Lam, David Marsden -- Skill Demands and Developments in the Advanced Economies / Caroline Smith -- Approaches to Skills in the Asian Developmental States / Johnny Sung, Arwen Raddon -- Emerging Economic Powers: The Transformation of the Skills Systems in China and India / Mingwei Liu, David Finegold -- Projecting the Impact of IT on Work and Skills in the 2030s / Stuart W. Elliott -- International Skill Flows and Migration / James Wickham -- Professional Skills: Impact of Comparative Political Economy / Mari Sako -- Skills and Training for the Older Population: Training the New Work Generation / Wendy Loretto, Chris Phillipson, Sarah Vickerstaff -- The Changing Meaning of Skill: Still Contested, Still Important / Jonathan P
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Occupational training